Strategi Pemilihan Lokasi Belanja Berdasarkan Motivasi Pembelian dan Keputusan Konsumen - Rolyana Ferinia Pintauli; Michael Sabato Simatupang (Jurnal Simki Economic, 2024)
The consumer's selection is a key aspect in addressing the wants or desires of each individual. The problem arise, when shopping, a consumer's decision to select the necessary things can become uncertain. This situation is caused by a consumer's lack of motivation. This study attempts to examine the effect of shopping motivation on customer decisions in choosing retail locations in order to identify conditional difficulties. The survey was done quantitatively with 66 respondents and sent via the G-Form to customers who had shopping experiences in various shopping locations. The data was analyzed using multiple linear regression to determine the association between shopping motivation and consumer decision making. The study's findings indicate that shopping motive has a substantial influence on customer decisions about where to purchase. Understanding the many factors underpinning consumer decision making allows merchants to tailor their marketing efforts to better meet the demands and preferences of their customers. The strategy is that retailers can strategically position their stores in shopping centers or social centers to serve socially motivated buyers by segmenting the market based on shopping purposes.